Analisis Efisiensi Saluran Pemasaran Jamur Tiram Di Kabupaten Purbalingga - Eneng Mia Saptarini; Lilis Siti Badriah; Istiqomah Istiqomah (UIN Siber Syekh Nurjati Cirebon, 2019)
ABSTRACT This study aims to analyze the income received by farmers and to measure the marketing efficiency of oyster mushroom in Purbalingga Regency. It used survey method with primary data collected through questionnaire-based interviews. The sample consists of 22 farmers using census and 24 intermediary traders obtained by snowball sampling. Data analysis techniques used in this study are income analysis, marketing margin, farmer's share, marketing costs, marketing profit and marketing efficiency. The results show that there are three marketing channels for oyster mushroom in Purbalingga: channel I (farmers ─ consumers), channel II (farmers ─ village collectors ─ retailers ─ consumers), and channel III (farmers ─ village collectors ─ wholesalers ─ processor ─ consumers). The results show that the marketing of oyster mushrooms in Purbalingga Regency has not been efficient. The study also indicates that the shorter the marketing channel, the greater the farmer's share. Therefore farmers and the local government should take efforts to shorten the marketing channel. Keywords: revenue, marketing channels, marketing margin, farmer's share, marketing costs, marketing profit, and marketing efficiency